Gestión de residuos sólidos domiciliarios y cumplimiento de objetivos de desarrollo sostenible en el distrito de San Juan Bautista, 2021 - Freitas Vigo, Hector (2023)
The objective of this research was to determine the relationship between the Management of household solid waste and compliance with sustainable development objectives in the district of San Juan Bautista 2021, the study chose to be of an applied type, quantitative approach, correlational descriptive level and design not experimental; whose study population was 32 officials, the survey was used as a technique and the questionnaire as an instrument for data collection. According to the results, it was determined that solid waste management was rated as efficient (50%) since the Municipality almost always demonstrates commitment to the waste collection and transportation service; likewise, that they almost always establish regulations for the regulation of household solid waste management; On the other hand, the fulfillment of sustainable development objectives has been developing efficiently (56%) since sustainable jobs are almost always created to give work to more people, in addition, they almost always implement universal policies that seek equality and opportunities; Likewise, cooperation between local producers is almost always promoted to improve the supply chain. Concluding that there is a relationship between waste management and compliance with sustainable development objectives, corroborated by a coefficient and significance of (r=0.612; p=0.000).